Studi Peradaban Islam Pada Masa Daulah Fathimiyah - Indah Syafiqah Lubis (IAIN Bengkulu, 2023)
The controversy raised by the Fathimiyah Daula in the history of Islamic civilization is really interesting to discuss and review. The greatest contribution to Islamic civilization was given by the Fathimiyah dynasty because of Al-Azhar University in Cairo, which is still used and utilized today. Talking about the ideology and understanding held by Daulah is a Shia understanding. Loyalty to Ali bin Abi Talib is the most important topic for the Shiites. This dynasty is known as an extreme dynasty because it contains a lot of blasphemy, fraud and murder. The Fatimid Daulah has three capital cities including Raqadah, al-Mahdiyah and Cairo along with the leadership of 14 caliphs for 262 years maximum in 909 to 1171. So this research is written to discuss the development until the decline of the Fatimid Daulah. How is the history of the Fathimiyah Daula, the development of the Fathimiyah in the political, social, religious, educational, economic fields. The researcher will also review the journey of Daulah Fathimiyah from its heyday to the downfall of Daulah Fathimiyah. Kontroversi yang ditimbulkan oleh Daulah Fathimiyah pada sejarah peradaban Islam sunggu menarik untuk dibahas dan diulas. Sumbangsih teresar dalam peradaban Islam diberikan oleh Dinasti Fathimiyah karena Universitas Al- Azhar Kairo yang sampai saat ini masih digunakan dan dimanfaatkan. Berbicara mengenai ideologi dan pemahaman yang dianut oleh Daulah ini adalah pemahaman syi’ah. Kesetiaan akan Ali bin Abi Thalib adalah topik yang paling penting pada kaum syi’ah. Dinasti ini dikenal dengan dinasti yang ekstrim karena didalamnya banyak penistaan, penipuan juga pembunuhan. Daulah Fatimiyah memiliki tiga ibu kota diantaranya adalah Raqadah, al-Mahdiyah dan Kairo sepanjang pimpinan 14 khalifah selama 262 tahun lamanya tepatnya pada tahun 909 sampai 1171. Maka dari penelitian ini ditulis untuk membahas mengenai kejayaan sampai kemunduran Daulah Fathimiyah. Bagaimana perjalanan sejarah Daulah Fathimiyah, perkembangan bani Fathimiyah dalam bidang politik, social, agama, Pendidikan, ekonomi. Peneliti juga akan mengulas perjalanan Daulah Fathimiyah dari masa kejayaan sampai masa keruntuhan Daulah Fathimiyah.